The Impact of Dialects and Linguistic Diversity within the Spanish-Speaking World ‎on Education: Examining how Teachers can Address Dialect and Cultural Diversity ‎in Teaching Spanish - Lamees Allouzi; Ali Alewaidat (دراسات: العلوم التربوية)
Objectives: This study aims to investigate the impact of dialects and linguistic diversity within the Spanish-speaking world on education, focusing on how teachers can effectively address this diversity in their Spanish language instruction.